PENGARUH TOTAL ASSET TURNOVER (TATO), FIRM SIZE DAN DEBT TO EQUITY RATIO (DER) TERHADAP PROFITABILITAS PERUSAHAAN PADA PT. PANCA GLOBAL KAPITAL TBK PERIODE 2010-2024 - Sania Eka Putri; Rahma NiaIvanka; Nadiatuz Zahra; Muhamad Rafi Ibrahim; Farrel Rasendrya Hartanto; Fazhar Sumantri (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the influence of Total Asset Turnover (TATO), Firm Size, and Debt to Equity (DER) on corporate profitability, as measured by Return on Asset (ROA), at PT Panca Global Kapital Tbk for the period 2010-2024. The research is grounded in profitability theory and financial ratio analysis, which posits that asset management efficiency, firm scale, and capital structure can affect a company’s ability to generate profits. The methodological approach employed is quantitative, characterized by descriptive and verificative elements. Secondary data in the form of the company’s annual financial reports, sourced from the official company website, were utilized. Data analysis was conducted using classical assumption test, multiple linear regression, coefficient of determination test, t–test, f-test, facilitated by IBM SPSS Statistic 27 software. The findings indicate that TATO and Firm Size exert a positive and significant influence on ROA. Simultaneosly, the three independent variables significantly influence corporate profitability, with a coefficient and firm value of 98%. This study concludes that asset management efficiency and firm scale constitute key factors in enhancing corporate profitability.